Transcriptome profiling of raspberry (Rubus idaeus Var. Amira) in response to infection by tomato ringspot virus (ToRSV) - Gloria González; Felipe Aguilera; Vívian D'Afonseca (Heliyon, 2020)
Raspberry (Rubus sp.) is a berries fruit with an ongoing agricultural and commercial interest due to its high contents of flavonoids and nutrients beneficial for human health. The growing demand for raspberries is facing great challenges associated mainly with the dispersal of diseases, which produces a decrease in productivity and fruit quality. A broad range of genomic resources is available for other Rosaceae species; however, genomic resources for species of the Rubus genus are still limited. Here, we characterize the transcriptome of the Rubus idaeus (Var. Amira) in order to 1) provide clues in the transcriptional changes of R. idaeus against tomato ringspot virus (ToRSV); and 2) generate genomic resources for this economically important species. We generate more than 200 million sequencing reads from two mRNA samples of raspberry, infected and not infected by ToRSV, using Illumina technology. After de novo assembly, we obtained 68,853 predicted protein-coding sequences of which 71.3% and 61.3% were annotated using Gene Ontology and Pfam databases, respectively. Moreover, we find 2,340 genes with differential expression between raspberries infected and not infected by ToRSV. Analysis of these genes shows functional enrichments of the oxidation-reduction process, cell wall biogenesis, terpene synthase activity, and lyase activity. These genes could be involved in the raspberry immune response through the interaction of different metabolic pathways; however, this statement needs further investigations. Up-regulation of genes encoding terpene synthases, multicopper oxidases, laccases, and beta-glucosidases might suggest that these enzymes appear to be the predominant transcriptome immune response of R. idaeus against ToRSV. Furthermore, we identify thousands of molecular markers (i.e., SSRs and SNPs), increasing considerably the genomic resources currently available for raspberries. This study is the first report on investigating the transcriptional changes of R. idaeus against ToRSV.